Advanced Tribology 2009
DOI: 10.1007/978-3-642-03653-8_59
|View full text |Cite
|
Sign up to set email alerts
|

Pitting Life Prediction Based on a 3-D Line Contact Mixed EHL Analysis and Subsurface von Mises Stress Calculation

Abstract: Surface pitting due to contact fatigue is a major failure mode of many mechanical components, such as various gears and rolling element bearings. Pitting life prediction, therefore, is vital to design and performance/reliability improvements. Conventional prediction methods, commonly found in industrial standards, are based on the Hertzian contact theory under assumptions that surfaces are ideally smooth with no lubrication. The present study aims to develop a von Mises stress-based pitting life prediction app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Detailed discussion on this fatigue model for RCF of surfaces subjected to mixed lubrication can be found in the papers by. Epstein et al [27] and Zhu et al [28].…”
Section: The Fatigue Life Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed discussion on this fatigue model for RCF of surfaces subjected to mixed lubrication can be found in the papers by. Epstein et al [27] and Zhu et al [28].…”
Section: The Fatigue Life Modelmentioning
confidence: 99%
“…The first unified mixed EHL model for point contact problems with 3-dimensional (3D) machined roughness was presented by Zhu and Hu, 1999 [24], Hu and Zhu, 2000 [25], and Zhu [26] et al, which has been demonstrated to be capable of simulating the entire transition from the full-film and mixed lubrication all the way down to the boundary lubrication and dry contact. This mixed EHL model and the subsurfacestress-based fatigue-life model by Zaretsky [12] have resulted in effective approaches for pitting life predictions by Epstein et al [27], Zhu et al [28], Greco et al [29], and others. However, no sliding effect was considered in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the stress-based fatigue life model proposed by Zaretsky [22] has been utilized for fatigue life prediction. is fatigue model has been widely adopted by the other research groups [11,13,21]. e model can be expressed as…”
Section: Fatigue Life Prediction Modelmentioning
confidence: 99%
“…Masjedi and Khonsari [10] conducted a starved mixed EHL model for line and point contacts considering the surface roughness and studied the influence of starved oil on the interaction of oil film thickness and surface roughness. Zhu et al [11] established a deterministic mixed EHL model of finite roller contact involving realistic surface roughness and studied the effect of roller length and crown radius on the film thickness, subsurface stress field, and so on. Torabi et al [12] proposed a mixed EHL model of a finite length cam and follower mechanism considering surface roughness and studied the influence of thermal effects, end leakage, and roughness on the friction performance.…”
Section: Introductionmentioning
confidence: 99%
“…Any attempt to apply fatigue models to the surface layers that experience the transient cyclic loading associated with asperity interactions in mixed lubrication needs to take residual stress into account. Initial attempts to carry out this kind of fatigue modelling are promising [39,40] but perhaps oversimplify what is an elastic-plastic loading scenario with residual stress and potentially important strain hardening effects. But even the first approximation of this approach using elastic loading is potentially very useful in distinguishing between the fatigue effects that can be expected with different kinds of surface roughness.…”
Section: Surface Degradationmentioning
confidence: 99%